2017
DOI: 10.1155/2017/9701978
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Complexion between Cold‐ and Heat‐Prescription Groups in Sasang Medicine

Abstract: Sasang constitutional medicine (SCM) is a type of traditional Korean medicine (TKM) that classifies the human constitution into four types. The appearance of the complexion is one of the diagnostic factors of SCM but is rarely used in a quantitative and objective manner for diagnosis. In this study, an analysis using actual clinical data was conducted to assess the use of the complexion as a diagnostic element. A total of 528 Sasang medicine prescriptions from Korea Constitutional Multicenter Bank (KCMB) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…In terms of facial variables used in our study, facial characteristics (shape) and complexion (color of face) were often used to diagnose diseases or prescribe herbal medicine, such as Taeumjowi-tang [35][36][37]. For example, Park et al [35] investigated the association of facial complexion with age, BMI, and systolic blood pressure for cold-and heat-prescription, such as Taeumjowi-tang, and documented significant differences in complexion between cold-prescription and heat-prescription subjects. This implies that prescriptions such as Taeumjowi-tang may differ according to individual patterns and that the efficacy of herbal medicine may differ according to individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of facial variables used in our study, facial characteristics (shape) and complexion (color of face) were often used to diagnose diseases or prescribe herbal medicine, such as Taeumjowi-tang [35][36][37]. For example, Park et al [35] investigated the association of facial complexion with age, BMI, and systolic blood pressure for cold-and heat-prescription, such as Taeumjowi-tang, and documented significant differences in complexion between cold-prescription and heat-prescription subjects. This implies that prescriptions such as Taeumjowi-tang may differ according to individual patterns and that the efficacy of herbal medicine may differ according to individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A frontal full-face photograph was taken with a neutral expression using a Nikon D700/D5100 digital camera with an 85 mm lens under bilateral illumination at a fixed subject-camera distance of 1.6 m. A color chart used for color correction was attached to a ruler that was placed approximately 1 cm below the chin ( Figure 1 ) [ 23 ]. All subjects were requested to present their natural fresh-face without any makeup.…”
Section: Methodsmentioning
confidence: 99%
“… Three regions of facial complexion (forehead, cheek, and nose) [ 23 ]. Light green lines and nodes show the grid and facial landmarks used for the construction of facial regions, along with a color chart used for color correction placed below the chin.…”
Section: Figurementioning
confidence: 99%
“…In addition, SCM specialists had strongly accounted for facial features as one of the most reliable elements in distinguishing Sasang types [ 23 ]. Many studies had been conducted and facial features were shown to be highly employed in the determination of Sasang types [ 6 , 16 , 24 – 26 ]. Another study had also mentioned that face shape was found to be more utilized among all the facial elements.…”
Section: Introductionmentioning
confidence: 99%